Fabrication of carbon-based nanostructured flexible supercapacitor - Chee, Wei Kit (2018)
This research essentially focuses on the fabrication of a carbon-based flexible energy storage devices via the development of highly flexible electrode material. In the first study where polypyrrole/ graphene oxide/ zinc oxide nanocomposite was directly electrodeposited on a nickel foam by an electrodeposition technique, a free-standing flexible supercapacitor was fabricated by sandwiching a potassium hydroxide/ polyvinyl alcohol hydrogel electrolyte between two layers of the as-prepared ternary nanocomposite electrodes. A specific capacitance of 123.8 Fg-1 at 1 Ag-1 was achieved with excellent flexibility. However, the cycling stability of the ternary nanocomposite showed a sensitive behavior towards types of electrolyte used, at which a favorable specific capacitance retention of more than 90.0% using a mild alkaline electrolyte. In order to improve the stability performance, electrospinning technique is employed at which a flexible and conductive nanofiber membranes were fabricated. Initial attempt by introducing graphene oxide to envelop the carbon nanofibers resulted poor electrochemical performance as the effect of pore blockage by graphene oxide. Whereby second attempt with addition of graphene nanoplatlets resulted in enhancement of electrochemical performance, however with in-distinctive trend as the effect of phase separation presence between CNF/ GnP components. Further modification was made at which graphene oxide was functionalized to induce hydrophobicity by using a photo-polymerization approach, at which it was successfully dispersed in the precursor polymeric solution. The electrochemical performance of the reduced graphene oxide-modified carbon nanofibers resulted in a specific capacitance of 140.10 Fg-1 at a current density of 1Ag-1 with capactitance retention of 96.2%, however with a significant increase in charge transfer resistance, which was not favorable in electrochemical devices. A final attempt was made via electrospun polyacrylonitrile membranes with reinforcement of metallic contents, which induced a unique morphology with integration of metal oxides with the polymer structure upon carbonization. When the nanofibers were constructed into a supercapacitor device, a specific capacitance of more than 100 Fg-1 was recorded at 1 Ag-1, along with minimal resistance as compared to any other counterparts, achieved with reinforcement of nickel oxide nanoparticles. Furthermore, the fabricated device retained a capacitive retention of as high as 93.9% even after 2000 cycles of vigorous galvanostatic charging/ discharging process, with a minimal value of 0.05 V voltage drop. Additionally, the device successfully demonstrated excellent flexibility by recording no deviation in performance even subjected to bending and curvatures. These studies concluded that the fabrication of flexible electrode materials is the determining role in the fabrication of a highly flexible energy storage device.